Pediatric Neurogastroenterology : Gastrointestinal Motility and Functional Disorders in Children - Faure, Christophe; Thapar, Nikhil; Di Lorenzo, Carlo (Springer International Publishing : Imprint: Springer, 2017)
This volume provides a comprehensive and up-to-date theoretical review and practical guide on pediatric gastrointestinal motility and functional disorders. The latest edition includes extensively revised and new chapters to reflect the rapidly growing field of pediatric neurogastroenterology. New topics covered include neurobiology of pain in children, functional oropharyngoesophageal assessment, dysautonomia, and psychotropic drugs. The text also features instructive illustrations, photographs, and tables. Written by world-renown experts in the field, Pediatric Neurogastroenterology: Gastrointestinal Motility and Functional Disorders in Children, Second Edition is a valuable resource for pediatric gastroenterologists, adult gastroenterologists, pediatricians, and all professionals involved in the treatment and management of children with such disorders. .